Attachment and Socio‐Emotional Skills: A Comparison of Depressed Inpatients, Institutionalized Delinquents and Control Adolescents. (28th February 2012) - Delhaye, Marie; Kempenaers, Chantal; Stroobants, Rob; Goossens, Luc; Linkowski, Paul
Abstract : This study compared 50 depressed inpatients, 51 institutionalized delinquents and 51 control adolescents (total n = 152) regarding attachment and associated socio‐emotional skills. All of the participants took an individual interview (i.e., anamnesis, diagnostic interview and intelligence test) and completed the attachment measure and self‐report measures of socio‐emotional skills (i.e., emotional intelligence, empathy and resilience). Results showed that controls scored higher on secure attachment, whereas both of the other groups scored higher on preoccupied attachment. Depressed adolescents had lower scores on emotional intelligence than did controls. Finally, depressed adolescents had lower scores than the other two groups on resilience. The anxious or preoccupied attachment in both clinical groups, the overall frailty of depressive adolescents and the apparent resilience of delinquent adolescents despite their cognitive limitations should inform the respective treatment plans for these groups of adolescents. Suggestions for future research into differences between depressed and delinquent adolescents are outlined. Copyright © 2012 John Wiley & Sons, Ltd. Key Practitioner Message: Both depressed and delinquent adolescents show more anxious attachment. Depressed adolescents are less resilient than delinquent adolescents. Delinquent adolescents are less intelligent than the other two groups but well‐adjusted overall. These differences should inform treatment plans for these two clinical groups.